Shopping cart - Thara’a Abu hamed; Shorouq ishtaiah (My University, 2021)
Shopping cart With human needs constantly renewed, his need to buy does not stop, And because the buying and shopping process consumes a lot of time, we tried to find a helpful idea for both the customer and the cashier, in order to reduce the effort for both of them using the shopping cart that operates with a smart system .we deal with the problem of the long role in stores and stores, where we will create a shopping cart that will have a scanner to scan all purchases from the buyer’s side, in addition to a screen to see prices before putting them in the basket and once it reaches the cashier, the payment will be on the final product, and to ensure that there is no Fraud on the part of the buyer We will design the basket in the form of two boxes, one of which is open to place unconfirmed purchases and the second is closed. It does not open until after scanning the barcode of the product and opens only temporarily and then can be opened when reaching the cashier, also we will use data base to store all products and also there is a connection between the cart and the cashier via Wireless. Also we will use sensors to ensure that the buyer had put the product before close the closed cart.